Commodified and Criminalized: New Racism and African Americans in Contemporary Sports - Leonard, David J.; King, C. Richard (Rowman & Littlefield Publishers, 2010)
Commodified and Criminalized examines the centrality of sport to discussions of racial ideologies and racist practices in the 21st century. It disputes familiar refrains of racial progress, arguing that athletes sit in a contradictory position masked by the logics of new racism and dominant white racial frames. Contributors discuss athletes ranging from Tiger Woods and Serena Williams to Freddy Adu and Shani Davis. Through dynamic case studies, Commodified and Criminalized unpacks the conversation between black athletes and colorblind discourse, while challenging the assumptions of contemporary sports culture. The contributors in this provocative collection push the conversation beyond the playing field and beyond the racial landscape of sports culture to explore the connections between sports representations and a broader history of racialized violence.